The Handbook of textile culture - Jefferies, Janis; Conroy, Diana Wood; Clark, Hazel (London Bloomsbury, 2016)
In recent years, the study of textiles and culture has become a dynamic field of scholarship, reflecting new global, material and technological possibilities. This is the first handbook of specially commissioned essays to provide a guide to the major strands of critical work around textiles past and present and to draw upon the work of artists and designers as well as researchers in textiles studies. The handbook offers an authoritative and wide-ranging guide to the topics, issues, and questions that are central to the study of textiles today: it examines how material practices reflect cross-cultural influences; it explores textiles relationships to history, memory, place, and social and technological change; and considers their influence on fashion and design, sustainable production, craft, architecture, curation and contemporary textile art practice. This illustrated volume will be essential reading for students and scholars involved in research on textiles and related subjects such as dress, costume and fashion, feminism and gender, art and design, and cultural history.
1. New approaches to textile design / Hazel Clark -- 2. Views from Australia and the Asia Pacific / Diana Wood Conroy -- 3. Curating textiles : stuff that matters / Sara Martinetti, Alice Motard and Alex Sainsbury ; an interview with Seth Siegelaub -- 4. Textiles and architecture / Bradley Quinn -- 5. Patchworking ways of knowing and making / Kristina Lindström and Åsa Ståhl -- 6. Making known : the textiles toolbox - psychoanalysis of nine types of textile thinking / Claire Pajaczkowska -- 7. Binding autobiographies : a Jewishing cloth / Katya Oicherman -- 8. Materials, memories and metaphors : the textile self re/collected / Solveigh Goett -- 9. Archives of cloth : shadows of the past in re-visioning textiles / Diana Wood Conroy -- 10. Lived lives : materializing stories of young Irish suicide / Seamus McGuinness -- 11. Performing globalization in the textile industry : Anne Wilson and Mandy Cano Villalobos / Lisa Vinebaum -- 12. Changing perceptions of curatorial practice in South Asian and Commonwealth textiles / Jasleen Dhamija -- 13. Quilts for the twenty-first century : activism in the expanded field of quilting / Kirsty Robertson -- 14. Transforming Malaysian hand woven songket in the contemporary world / June Ngo Siok Kheng -- 15. Creative resilience thinking in textiles and fashion / Mathilda Tham -- 16. Use your illusion : dazzle, deceit and the 'vicious problem' of textiles and fashion / Otto von Busch -- 17. Curating extreme textiles : designing for high performance / Matilda McQuaid -- 18. Social fabric : textiles, art, society and politics / Christine Checinska and Grant Watson -- 19. Yuta djama : innovation in Australian Indigenous fibre / Margie West -- 20. Kaunas Biennial : spindling from textile to public culture / Ed Carroll -- 21. A view from elsewhere : a global stage - curating textiles from the Asia Pacific / Ruth McDougall -- 22. Envisioning fibre in the cultural heritage of Hangzhou, China / Shi Hui and Xu Jia -- 23. The Lausanne International Tapestry Biennials (1962-1995) / Giselle Eberhard Cotton -- 24. The fabric of memory : towards the ontology of contemporary textiles / Sara Diamond -- 25. Indigo dyeing in the land of its origin : history unknown / Smritikumar Sarkar -- 26. Feeling : sensing the affectivity of emotional politics through textiles / Agnieszka Golda -- 27. Reviving kapiak : exploring the material identity of barkcloth in a Melanesian society / Graeme Were -- 28. Roundtable discussions and concluding comments / Janis Jefferies and Diana Wood Conroy.
Includes bibliographical references and index.
Keywords: Textile design; Textile design -- Social aspects; Textile crafts -- Social aspects; Textile fabrics -- Social aspects